2020
DOI: 10.17576/pengurusan-2020-58-08
|View full text |Cite
|
Sign up to set email alerts
|

The Minang - Nomads Businesses’ Performance: The Role of Proactive Personality, Creativity and Innovative Work Behavior

Abstract: Amid the prevalence of particular ethnic supremacy in entrepreneurship, few have looked at the centrality of entrepreneurship in various cultural domains. Authors utilize human capital formation theory to assert that extended family provide a crucial background in the growth of individual business skills and preferences. This study aims at investigating the influence of proactive personality and creativity on small businesses performance owned by the member of Minang business community through the mediating ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 103 publications
(136 reference statements)
2
14
0
Order By: Relevance
“…The fifth hypothesis is valid (H5 accepted). It is consistent with previous studies, which indicated that a proactive personality is favorably associated with self-efficacy role breadth [ 39 ]. The present study also revealed that when rehabilitation officers speak to proactive personality, they refer to those who can take action, play a more flexible role, and make adjustments akin to mastery or control [ 3 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fifth hypothesis is valid (H5 accepted). It is consistent with previous studies, which indicated that a proactive personality is favorably associated with self-efficacy role breadth [ 39 ]. The present study also revealed that when rehabilitation officers speak to proactive personality, they refer to those who can take action, play a more flexible role, and make adjustments akin to mastery or control [ 3 ].…”
Section: Discussionsupporting
confidence: 93%
“…Previous research has shown that proactive personality is well connected to role breadth self-efficacy in a substantial way [ 36 ]. It is consistent with the findings of [ 39 ], which indicated that a proactive personality is favorably associated with self-efficacy role breadth. According to the findings, proactive personality and creativity have a beneficial influence on creative behavior and, consequently, organizational effectiveness.…”
Section: Literature Reviewsupporting
confidence: 92%
“…For example, the ability to have a more adaptable role orientation as well as control (Parker and Sprigg, 1999). According to Andri et al (2020), PP is connected to RBSE in a substantial way. When people with PP feel they can effectively start an organization, they are more inclined to do so (Travis and Freeman, 2017).…”
Section: Proactive Personality On Role Breadth Self-efficacymentioning
confidence: 99%
“…Budiningsih et al [12] explained that the ability of innovation is efforts made to find, produce, introduce and apply a new finding in the form of ideas and solutions, technology that is useful for every human activity/ business indicated to be: looking/ seeing opportunities/ opportunities, building/ issuing ideas, seeking support for implementation and realizing/ applying new ideas. Andri et al [13] claim that innovative behavior is an output of productive idea development to enhance processes, procedures, and products.…”
Section: Innovation Skillsmentioning
confidence: 99%